Improved Detection of Circulating miRNAs in Serum and Plasma Following Rapid Heat/Freeze Cycling - Mariner, Peter D.; Korst, Armin; Karimpour-Fard, Anis; Stauffer, Brian L.; Miyamoto, Shelley D.; Sucharov, Carmen C. (MicroRNA, 2018)
Background: The measurement of circulating miRNAs has proven to be a powerful biomarker tool for several disease processes. Current protocols for the detection of miRNAs usually involve an RNA extraction step, requiring a substantial volume of patient serum or plasma to obtain sufficient input material. Objective: Here, we describe a novel methodology that allows detection of a large number of miRNAs from a small volume of serum or plasma without the need for RNA extraction. Methods: Three μl of serum or plasma was subjected to three cycles of high and low temperatures (heat/freeze cycles) followed by miRNA arrays. Results: Our results indicate that miRNA detection following this process is highly reproducible when comparing multiple samples from the same subject. Moreover, this protocol increases the reproducibility of miRNA detection in samples that were previously subjected to multiple freeze-thaw cycles. Importantly, the detection of miRNAs from serum vs. plasma following heat/freeze cycling are highly comparable, indicating that this heat/freeze process effectively eliminates differences in detection between serum and plasma samples that have been reported using other sample preparation methodologies. Conclusion: We propose that this method is a potent alternative to current RNA extraction protocols, substantially reducing the amount of sample necessary for miRNA detection while simultaneously improving miRNA detection and reproducibility.
Keywords: plasma